2014
DOI: 10.1128/jvi.00738-14
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Coronavirus RNA Replication on an NH 2 -Terminal Partial Nonstructural Protein 1 in cis

Abstract: Genomes of positive (؉)-strand RNA viruses use cis-acting signals to direct both translation and replication. Here we examine two 5=-proximal cis-replication signals of different character in a defective interfering (DI) RNA of the bovine coronavirus (BCoV) that map within a 322-nucleotide (nt) sequence (136 nt from the genomic 5= untranslated region and 186 nt from the nonstructural protein 1 [nsp1]-coding region) not found in the otherwise-identical nonreplicating subgenomic mRNA7 (sgmRNA7). The natural DI R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
(149 reference statements)
1
8
0
Order By: Relevance
“…The large number of covariant base pairs in the alphacoronavirus SL5 (Fig. 2) suggest significant constraints and a major functional role for this structure in alphacoronavirus (and, possibly, betacoronavirus) replication and there is indeed some experimental evidence to support this hypothesis (Brown et al, 2007;Su et al, 2014). Using RNA structure probing information obtained for the 5 -terminal 600 nts of HCoV-229E and HCoV-NL63, we confirmed and refined our RNA secondary structure predictions for two B-lineage alphacoronaviruses ( Figs.…”
Section: Characterization Of Alphacoronavirus 5 -Proximal Rna Structuressupporting
confidence: 76%
See 1 more Smart Citation
“…The large number of covariant base pairs in the alphacoronavirus SL5 (Fig. 2) suggest significant constraints and a major functional role for this structure in alphacoronavirus (and, possibly, betacoronavirus) replication and there is indeed some experimental evidence to support this hypothesis (Brown et al, 2007;Su et al, 2014). Using RNA structure probing information obtained for the 5 -terminal 600 nts of HCoV-229E and HCoV-NL63, we confirmed and refined our RNA secondary structure predictions for two B-lineage alphacoronaviruses ( Figs.…”
Section: Characterization Of Alphacoronavirus 5 -Proximal Rna Structuressupporting
confidence: 76%
“…A subsequent BCoV DI RNA mutagenesis study further suggested that this multipartite RNA structure may involve several stem-loop (sub)structures identified in earlier studies (Gustin et al, 2009;Raman and Brian, 2005) but require refolding of other RNA structures suggested earlier to be essential for DI RNA replication (Brown et al, 2007). The study by Su et al (2014) also identified an intriguing requirement in cis of an oligopeptide sequence in the Nproximal part of nsp1, suggesting that nsp1 may be an essential cis-acting protein factor in betacoronavirus replication, in addition to its multiple other functions (Brockway and Denison, 2005;Huang et al, 2011a,b;Kamitani et al, 2006Kamitani et al, , 2009Lei et al, 2013;Lokugamage et al, 2012;Narayanan et al, 2008a;Tanaka et al, 2012;Tohya et al, 2009;Wathelet et al, 2007;Züst et al, 2007). Possible interacting partners for nsp1 remain to be identified.…”
Section: Functional and Structural Features Of Coronavirus 5 Cis-actimentioning
confidence: 84%
“…An earlier study found that certain amino-terminal point mutations in nsp1 were severely debilitating or lethal for MHV (53), but, in retrospect, this may be attributable to disruption of cis-acting RNA structures overlapping the first half of the nsp1 ORF. A very recent analysis of the replication of a DI RNA of bovine coronavirus, which is closely related to MHV, found an absolute requirement for an intact stretch of coding sequence near the amino terminus of nsp1 (35). This nsp1 peptide was proposed to provide a means for DI RNA to be recruited to the preformed replication complexes of the helper virus.…”
Section: Discussionmentioning
confidence: 99%
“…The 5= ends of coronavirus genomes, including the 5= UTR and part of the nsp1 coding region, contain multiple cis-acting RNA structures that are critical for replication and transcription (34). In MHV and other betacoronaviruses, the genus in which these structures have been most extensively studied, the genomic 5= end contains a series of at least eight stem-loops (SL) (35)(36)(37)(38)(39), as well as a four-way junction formed by a long-range interaction between the regions upstream of SL 5 (SL5) and downstream of SL7 (40) ( Fig. 2A).…”
Section: Construction Of a Mutant Containing Nsp3 As The First Subunimentioning
confidence: 99%
See 1 more Smart Citation